2014
DOI: 10.1177/2150135113501900
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of a Neonate With Medium Chain Acyl-Coenzyme A Dehydrogenase Deficiency Using Extracorporeal Life Support

Abstract: We report a neonate with medium chain acyl-coenzyme A dehydrogenase deficiency (MCAD) who had a cardiac arrest due to ventricular tachycardia and fibrillation. Extracorporeal life support (ECLS) was deployed, from which the baby was subsequently separated and discharged from hospital. This case was a rare neonatal presentation of MCAD and an uncommon indication for ECLS. We discuss the presentations of patients with MCAD and the use of ECLS for patients with possible inborn errors of metabolism and other unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Kumar et al described a neonate with MCAD (Medium Chain Acyl-CoA Dehydrogenase) deficiency, who was successfully resuscitated with ECMO, following an episode of VT progressing to VF. The authors concluded that ECMO support is not necessarily contraindicated in cases of inborn errors of metabolism, and can lead to excellent result [8]. In case series of 18 patients with VLCAD deficiency, out of 12 who presented with cardiomyopathy, one patient was treated with ECMO with good outcome (described shortly as survival during follow up period, [9]).…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al described a neonate with MCAD (Medium Chain Acyl-CoA Dehydrogenase) deficiency, who was successfully resuscitated with ECMO, following an episode of VT progressing to VF. The authors concluded that ECMO support is not necessarily contraindicated in cases of inborn errors of metabolism, and can lead to excellent result [8]. In case series of 18 patients with VLCAD deficiency, out of 12 who presented with cardiomyopathy, one patient was treated with ECMO with good outcome (described shortly as survival during follow up period, [9]).…”
Section: Discussionmentioning
confidence: 99%